2017
DOI: 10.3233/wor-172508
|View full text |Cite
|
Sign up to set email alerts
|

The application of a feasible exercise training program in the office setting

Abstract: The exercise training program designed in this study not only can effectively reduce neck, shoulders, and lower back pains, but also can improve the ROM or flexibility of the office workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Seven studies were classified as high quality [15][16][17]20,[22][23][24], and four as low quality [18,19,21,25]. Randomization was performed in eight studies [15][16][17][18][20][21][22][23], seven specified the similarity between groups at baseline evaluation [16][17][18][19][20]22,23], and nine the inclusion and exclusion criteria [15][16][17][20][21][22][23][24][25]. Six studies applied a blinding procedure [15][16][17]20,22,23], and two performed an "intention-to-treat" analysis [15,23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were classified as high quality [15][16][17]20,[22][23][24], and four as low quality [18,19,21,25]. Randomization was performed in eight studies [15][16][17][18][20][21][22][23], seven specified the similarity between groups at baseline evaluation [16][17][18][19][20]22,23], and nine the inclusion and exclusion criteria [15][16][17][20][21][22][23][24][25]. Six studies applied a blinding procedure [15][16][17]20,22,23], and two performed an "intention-to-treat" analysis [15,23].…”
Section: Resultsmentioning
confidence: 99%
“…Qigong induced a significant improvement after 5 weeks (−58.7%) [15], while no significant modifications were found after home-based exercise [24]. Shariat and colleagues [18] found a 40% reduction in LBP after 11 weeks of web-based exercise, evaluating participants with the Cornell Musculoskeletal Disorders Questionnaire. In another study, the authors found a reduction of 89.1% after 6 months of exercise [16].…”
Section: Pain and Disabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…In 2016, there were two important researches in this area. At first, Shariat el al., showed the positive effect of 11 week-long office-based exercise training, with focus on low back pain among office workers in Malaysia (Shariat, Lam, Kargarfard, & Danaee, 2015), followed by Dalager et al, in a longitudinal study among 390 Danish office workers, who revealed that not all forms of exercise training can affect the score of pain in the low back (Dalager, Justesen, Murray, & Sjøgaard, 2016). Dalager et al, also introduced intelligent physical exercise training with high intensity for the treatment of low back pain among office workers.…”
Section: Introductionmentioning
confidence: 99%
“…The recovery tools represent an individual, coherent and effective method to address the psychological dimension of BP. The outcomes could connect to current approaches aiming at the integration of feasible physical activity programs into work settings [45]. Consequently, psychological and physical interventions could be combined to prevent BP.…”
Section: Limitations and Strengthsmentioning
confidence: 93%